Managing interrelated tensions in headquarters–subsidiary relationships: The case of a multinational hybrid organization - Ambos, Tina C; Fuchs, Sebastian H; Zimmermann, Alexander (Journal of International Business Studies, 2020)
Abstract While all multinational organizations face the challenge of managing tensions between local integration and global responsiveness, they are increasingly required to pursue additional, often paradoxical, objectives – such as social and commercial goals. However, we know little about how these tensions at the core of the MNC strategy interact. Based on an inductive qualitative study of four headquarters–subsidiary relationships in a Latin American Multinational Hybrid Organization, we develop a model showing the interplay of multiple tensions and management approaches to address them. This allows us to contribute to research on subsidiary roles, which we found to differ depending on how multiple tensions are addressed. Furthermore, we add to the literature on hybridity in multinational organizations by pointing out how regional differences between units of a single organization unfold. Finally, we provide some practical recommendations for the management of multinational hybrid organizations.